Analysis Technical and Allocative Efficiency of the Usage of CPO Production Factors In PT. Sandabi Indah Lestari, Padang Jaya Sub-Distrct, North Bengkulu Regency - Dwi Tia Sukmawati; Irnad Irnad; Bambang Sumantri (Badan Penerbitan Fakultas Pertanian (BPFP), 2020)
The present study was aimed to analyze the levels of technical and allocative efficiency of the usage of CPO production factors in PT. Sandabi Indah Lestari. The data being used was primary and secondary data. The data analysis to measure technical efficiency was Cobb-Douglas frontier production function and production elasticity value, while allocative efficiency was analyzed using NPMxi to Hxi ratio. The research result showed that fresh fruit bunch (TBS), indirect labor (TKTDL), and fiber (FB) had significant positive effect on CPO production in PT. Sandabi Indah Lestari, while direct labor (TKL), solar fuel (SR), CaCO3, and Nalco N 8507 (N8507) didn’t have significant positive or negative effect on CPO production in PT. Sandabi Indah Lestari. Fresh fruit bunch (TBS), indirect labor (TKTDL), and fiber (FB) were technically efficient (0<EP<1). Conversely, allocatively fresh fruit bunch (TBS), indirect labor (TKTDL), and fiber (FB) were’nt efficient (NPMxi/Hxi>1).